THE IMPACT OF STRESS ON STUDENTS ACADEMIC PERFORMANCE AND HOW TO DEAL WITH IT - Usmonova , Sharifa Gulamovna (Educational Research in Universal Sciences, 2023)
Being a student comes with its fair share of challenges, and one of the most common hurdles is dealing with academic pressure. The demands of coursework, exams, and assignments can often lead to stress and overwhelm. However, learning effective stress management techniques is crucial for students to navigate their academic journey successfully while maintaining a balanced and healthy lifestyle. In this article, we will explore the strategies tailored specifically to students to cope with academic pressure, how students can manage stress and achieve a sense of balance.